Percorrer a vida e inventar mapas: desenho e cartografia como modos de fazer etnografia - Virginio, Stephanie da Motta (2025)
Tracing life and inventing maps is an ethnographic research carried out in Santa Maria, Brazil, between 2023 and 2025. It investigates drawing and cartography as ethnographic tools in contexts of mental health care and climate-related crises. The research unfolded in two main field sites: at the drawing table of CAPS II Prado Veppo, a community mental health service, and in Vila Ipiranga after the 2024 flood, accompanying therapeutic itineraries and community networks. More than representing territories, the maps created in these workshops produce territories, making visible the flows between bodies, places, and temporalities. Throughout the process, cartography revealed trajectories of care that remain invisible in institutional diagrams, exposing the relational meshes that sustain everyday life. Anchored in a relational and situated perspective, the research bridges ethnography and visual anthropology, taking drawing as both a political and epistemic gesture. The notion of graphic friction underscores that maps are not neutral artifacts: they challenge regimes of visibility, generate meaning, and open space for narratives, memories, and situated ways of inhabiting the city. These cartographic practices have also been transformed into territorial listening and collective planning tools in crisis contexts, expanding their impact beyond the fieldwork. This dissertation contributes to medical anthropology and visual anthropology by shifting cartography from a representational register to a shared invention, articulating ethnography, public policy, and lived experience.